2004
DOI: 10.1016/s0928-8244(03)00346-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugation methodology on the immunogenicity and protective efficacy of meningococcal group C polysaccharide–P64k protein conjugates

Abstract: Neisseria meningitidis serogroup C polysaccharide (CCPS) was conjugated to the carrier protein P64k using two different conjugation procedures, condensation mediated by carbodiimide with adipic acid dihydrazide as spacer and the reductive amination method. BALB/c mice were immunized with the resultant polysaccharide-protein conjugates and the immune response was evaluated. All conjugates assayed generated at least 10-fold higher antibody titers than the free polysaccharide. The reductive amination method rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The use of shorter saccharides has allowed the production of more defined and less crosslinked conjugates, with advantages in relation to reproducibility and vaccine characterization. Parameters, including conjugation chemistry (random against selective carbohydrate modification), linker used for coupling and saccharide chain length, can have an impact on the immunogenicity of the corresponding conjugate vaccines (53)(54)(55)(56). The effect of varying such parameters is antigen dependent and was investigated in the current study to optimize the design of a vaccine against MenX.…”
Section: Discussionmentioning
confidence: 99%
“…The use of shorter saccharides has allowed the production of more defined and less crosslinked conjugates, with advantages in relation to reproducibility and vaccine characterization. Parameters, including conjugation chemistry (random against selective carbohydrate modification), linker used for coupling and saccharide chain length, can have an impact on the immunogenicity of the corresponding conjugate vaccines (53)(54)(55)(56). The effect of varying such parameters is antigen dependent and was investigated in the current study to optimize the design of a vaccine against MenX.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a rational approach for using Bm95 as a novel carrier molecule for preventing infections caused by polysaccharide encapsulated bacteria was conceived. 42 The results obtained in this study showed high immunogenicity of the Bm95-based conjugate (MenCpSBm-ra) compared with the meningococcal C polysaccharide. Additionally, an enhanced immune response typical of the T-cell-dependent immune response against Men CpS was observed.…”
Section: Discussionmentioning
confidence: 56%
“…The mice were selected at random to form five groups with a total of five animals per group, and were maintained under controlled lighting conditions at 22°C, with access to water and laboratory chow ad libitum, as previously described. 42 The Bm95 conjugates and polysaccharides were mixed with incomplete Freund's adjuvant (Sigma-Aldrich, St Louis, MO, USA). The mice in group A were immunized with conjugated MenCpSBm-ra.…”
Section: Animals and Immunization Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For assaying meningococcal ACWY antibody (IgG) levels, plates were activated by adding 100 µl of 2 µg/ml poly L-lysine (Sigma-Aldrich, USA) in carbonate buffer at 37°C for 2 hours following previously detailed method [24]. After washing, plates were coated with 100µg/ml polysaccharide (NIBSC, London, UK) in PBS and incubated at 2-8°C overnight.…”
Section: Assessment Of Vaccine Safetymentioning
confidence: 99%